Bioavailability and mobility of copper and cadmium in polluted soil after phytostabilization using different plants aided by limestone. (March 2020) - Cui, Hongbiao; Li, Huiting; Zhang, Shiwen; Yi, Qitao; Zhou, Jing; Fang, Guodong; Zhou, Jun
Abstract: Phytostabilization aided by soil amendments has been advocated in areas contaminated by trace metals. In this study, the effects of indigenous weed ( Setaria pumila ), energy plant ( Pennisetum sinese ), cadmium (Cd)-hyperaccumulator (S edum plumbizincicola ), and copper (Cu)-tolerant plant ( Elsholtzia splendens ) on the bioavailability and mobility of Cu and Cd in polluted soil were evaluated after phytostabilization aided by limestone (0.1% wt) over four years. The four plants combined with limestone significantly increased soil pH and decreased Cu and Cd fractions extracted by NH4 OAc and diffusive gradients in thin films (DGT) than the untreated soils, respectively. P. sinese treatments decreased DGT-extractable Cu and Cd by 52.1% and 40.5% than S. pumila treatments, respectively. S. plumbizincicola and E. splendens treatments increased acid-soluble fraction of Cu and decreased residual fraction of Cu compared with S. pumila treatments. P. sinese treatments had the lowest phytotoxicity (inhibitoryrates, superoxide dismutase, peroxidase and catalase activities) among all treatments. Moreover, EDTA kinetic extraction showed that S. plumbizincicola and E. splendens treatments increased the mobility of Cu and Cd by increasing labile and less labile fractions of Cu and Cd compared with P. sinese treatments. Present results suggest that P. sinese is recommended as the remediation plant for phytoremediation aided by amendments. Highlights: A phytostabilization experiment aided by limestone was carried out in a polluted soil. P . sinese treatments decreased soil availability of Cu and Cd than E. splendens and S. plumbizincicola treatments. P. sinese treatments had the lowest phytotoxicity among all treatments. P. sinese treatments had the lowest mobility of Cu and Cd among all treatments. The energy plant P. sinese is recommended as remediation plant for phytoremediation.